Que vaut un négociant ? Prix et compétences des commerçants dauphinois, des années 1750 aux années 1820 - Boris Deschanel (Les Cahiers de Framespa)
The daily work of merchants and traders, in the eighteenth century, was the subject of many investigations by historians of commercial firms or commercial techniques. The organization of trading houses and the education of traders have been largely studied, but the effect of business skills on the business structures are less well known. Researchers often use the idea of « skill » and « experience », in order to explain the success or failure of agents. Through the example of French merchants from Dauphiné, this article studies how individuals negociated their value (or the value of their relatives and associates). It reconsiders the notion of business skill, as the result of social and symbolic relationships. It proposes to analyze the criteria that allow merchants to agree on the price of agents, especially in the context of contractual relations.